2018
DOI: 10.3390/su10041262
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Examination of Users’ Adoption of the Sharing Economy in China Using an Expanded Technology Acceptance Model

Abstract: With the popularity of sharing-based applications such as bicycle and car sharing, the sharing economy has attracted considerable global attention. The factors that affect users' adoption of the sharing economy must be identified to facilitate the promotion of low-carbon lifestyles and help enterprises attract more active users. By employing the technology acceptance model (TAM) and herd behavior, this study implemented an expanded TAM and identified several factors affecting behavioral intention (BI) toward t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 56 publications
(83 reference statements)
3
44
3
1
Order By: Relevance
“…On an individual level, herd behavior refers to the phenomenon of an individual following others' behaviors (e.g., Gao et al, 2018;Liu and Yang, 2018;Shantha, 2019). In psychology, herd behavior is understood as a behavior that irrationally and emotionally follows that of a crowd; some examples are riots, religious gatherings, and sporting events (e.g., Berger and Heath, 2008;Puaschunder, 2018;Allie and Ajiboye, 2019).…”
Section: Consumer Herd Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…On an individual level, herd behavior refers to the phenomenon of an individual following others' behaviors (e.g., Gao et al, 2018;Liu and Yang, 2018;Shantha, 2019). In psychology, herd behavior is understood as a behavior that irrationally and emotionally follows that of a crowd; some examples are riots, religious gatherings, and sporting events (e.g., Berger and Heath, 2008;Puaschunder, 2018;Allie and Ajiboye, 2019).…”
Section: Consumer Herd Behaviormentioning
confidence: 99%
“…Existing studies report that consumers, although they make rational choices, engage in herd behavior because they are cognitively lazy (e.g., Spiller and Belogolova, 2016;Liu and Yang, 2018;Allie and Ajiboye, 2019). As such, they often prefer simple to complex solutions; for example, they may prefer to rely on heuristics, such as group consensus, when making a decision (e.g., Puaschunder, 2018;Salcedo and Jiménez-Leal, 2019;Shantha, 2019).…”
Section: Consumer Herd Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…The footprint of sustainability can be followed in the SE by considering more efficient utilization of the resources, creating social capital, reducing economic activities, lowering environmental pollutions and empowering ordinary people [51,120]. Liu and Yang (2018) believe that developing SE is a way towards the adoption of sustainable lifestyles [58]. Stanković et al (2016) believe in equal levels of importance for economic, financial, ecological, and social values in the sharing economy for value sharing and creation [121].…”
Section: Sustainabilitymentioning
confidence: 99%
“…The study found that sensitivity to time is found to be the vital factor affecting transfer willingness. Liu and Yang [29] tried to identify factors that affect behavioral intention (BI) toward the sharing economy by expanding on the technology acceptance model. Throughout their study, they found that perceived usefulness (PU) and perceived ease of use (PEOU) are observed to be the key factors affecting BI.…”
mentioning
confidence: 99%